Islamic Education Thought Perspective of the Ikhwanus Shafa - Fathul Rahman (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
The Islamic religion has various figures who are very well known in the world of education. There are many thoughts from Muslim figures that are still being developed today and make a big contribution to the world of education. These contributions include education in the fields of philosophy, medicine, astronomy, mathematics, politics and many more in education. Like classical Muslim figures who are well-known in the world of education, Ikhwanus Shafa is also a thinker in Islamic education and a classical Muslim intellectual who has made reforms in the development of Islamic education in all scientific fields, especially in the field of education. Therefore, the author wants to describe the Islamic educational thought style from the Ikhwanus Shafa perspective. This research is included in qualitative research based on literature study. The data source in this research analyzes works, books and journals related to the figure Ikhwanus Shafa. The results of the research explain that the Ikhwanus Shafa's style of thinking in Islamic education starts from how to gain knowledge, type of teacher, educational goals, curriculum and teaching methods in Islam.